Study and analysis of maternal serum alpha-fetoprotein levels as a biomarker of placental adherence in low lying placenta - Kaur, Jashanjot; Kaur, Amrit Pal; Kaur, Sukhraj; Sidhu, Harjot Kaur (International Journal of Research in Medical Sciences, 2023)
Background: The objective was to study and analyze maternal serum alpha-fetoprotein levels as a biomarker of placental adherence in low lying placenta. Methods: This was a prospective observational study analysing the conditions and the data of 80 cases with low lying placenta in a tertiary care hospital. The analysis was done for the association of MSAFP with MRI, perinatal and maternal outcome. Results: The level of MSAFP was found higher in 12 out of 13 cases (93.3%) of placenta previa with placental adherence. There was significant surgical intervention (80%) and increased maternal morbidity (68.8%) in the study group with placental adherence and raised MSAFP respectively. Conclusions: MSAFP is an important biomarker for prognostication of placental adherence in low lying placenta.